REPRESENTANTION OF MASCULINITIES IN THE TEXTBOOK OF YOUTH AND ADULTS EDUCATION - Baptista, Rafael Ferraz (2020)
This paper intends to present a brief analysis on how masculinities are represented in the Youth and Adult Education textbook. Bibliographical research allowed the understanding that masculinity is characterized as social practices that define the patterns of male behaviors. Furthermore, it was possible to understand that hegemonic masculinity is the pattern one, which is at the top of the relations between the individuals and exerts coercion on others masculinities. Data collection was based on the choice of a textbook adopted in the municipal schools of Rio Claro, in the interior of São Paulo State, from which images representing men and women in diversified activities were extracted. These images were categorized in order to base and enable the analysis of the data obtained. It was noticed that the textbook was produced from logical-formal aspects, highlighting the empirical character of traditional pedagogy and that, consequently, reproduces the values of a hegemonic masculinity. It was also concluded that school practices, as well as resources, need to adopt actions that encourage/motivatethe production of theoretical thinking, enabling the formation of an individual capable of knowing, reflecting and acting on his reality.